# for sin(angle)+cos(angle)cot(angle)=csc(angle)-- prove the equation algebraically?

### 2 Answers | Add Yours

`cot(theta)=(cos(theta))/(sin(theta))` and

`sin^2(theta)+cos^2(theta) = 1` so

`sin(theta)+cos(theta)cot(theta) =`

`sin(theta)+cos(theta)(cos(theta))/(sin(theta)) =`

`(sin^2(theta))/(sin(theta))+(cos^2(theta))/(sin(theta)) =`

`(sin^2(theta)+cos^2(theta))/(sin(theta)) =`

`1/sin(theta) = csc(theta)`

sin+cos(cos/sin)

Common denominatior is sin so it becomes:

(sin^2+cos^2)/(sin)

We know that sin^2+cos^2 = 1 so on we get:

1/sin

Which is equal to csc of theta.